1999
DOI: 10.1002/(sici)1097-0185(19990201)254:2<298::aid-ar16>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical study of Magellanic penguin (Spheniscus magellanicus) minor salivary glands during postnatal growth

Abstract: The histological and histochemical features of the minor salivary glands during postnatal development have been generally associated with the type of food ingested. However, recent studies support the fact that these salivary glands develop independently of the diet; in fact, minor salivary glands have similar morphological and histochemical characteristics in adult individuals of species with different diet regimens. Thus, the aim of this study was to characterize the developmental morphology of the penguin m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 14 publications
(15 reference statements)
3
29
2
Order By: Relevance
“…This characteristics was also observed by Oliveira et al (2011) in Spheniscus magllanicus and Kobayashi et al (1998) in other four species of penguins: Spheniscus demersus, Pygoscelis papua, Spheniscus humboldti, and Eudyptes chrysolophus. The triangular shape with the pointed apex is considered the standard in omnivorous birds (GARDNER, 1927).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This characteristics was also observed by Oliveira et al (2011) in Spheniscus magllanicus and Kobayashi et al (1998) in other four species of penguins: Spheniscus demersus, Pygoscelis papua, Spheniscus humboldti, and Eudyptes chrysolophus. The triangular shape with the pointed apex is considered the standard in omnivorous birds (GARDNER, 1927).…”
Section: Discussionsupporting
confidence: 72%
“…However, Samar et al (1995;1999) observed in this species the presence of salivary glands in the back of the tongue, in the transition region with oropharynx and palate. Thus, one may suggest that humidification of food commences from the oropharynx, which facilitates swallowing of food, which in penguins is swallowed whole.…”
Section: Discussionmentioning
confidence: 66%
“…The salivary glands in birds are generally tubular in nature with serous elements usually being absent (Ziswiler & Farner 1972), a feature also apparent in the ratites. The lingual glands of the emu were similar to those depicted in other bird species, although the structural classifi cation differed (Samar et al 1999;Bacha & Bacha 2000;Liman et al 2001;AlMansour & Jarrar 2004;Jackowiak & Godynicki 2005).…”
Section: Glandssupporting
confidence: 52%
“…In the present study, we also found phospholipid in the secretory granules of the rat palatine gland acinar cells, being particularly abundant in glands at postnatal days 7 and 10. Smar et al 23) reported that Magellanic penguin palatine gland showed changes in its properties in addition to the amount of saliva it secreted during postnatal growth. Possibly in rats, phospholipid in saliva from the palatine gland might also protect the developing oral mucosa during suckling, because it was evident most conspicuously during early postnatal development and then disappeared almost entirely towards maturity.…”
Section: Action Of Phospholipid In Salivamentioning
confidence: 99%